Reformulasi Hukum Penguatan Koperasi Syariah di Indonesia - Ruben Panggabean (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
The absence of regulation implementations for Law No. 1 of 2013 about microfinance institutions can also be said to be a legal vacuum. As a result, violations of Law No. 1 of 2013 will be difficult to prosecute both administratively and criminally. Whereas, the administrative and criminal violation will clearly have direct consequences for the society both as depositors and Debtors. This research used normative juridical. The research method used in this research is normative juridical. In this research, an approach toward legislation was used, that is No. 1 of 2013 about Microfinance Institutions. Another consequence is an ineffective implementation of Law No. 1 of 2013 which has become legal basis for Microfinance Institutional operations legality and protection for the society as depositors and Debtors. Legal reformulation of Sharia Cooperation Strengthening in Indonesia was carried by constructing the implementation Rules as mandated by Law No. 1 of 2013 about Microfinance Institutions. An important thing of legal reformulation made in the implementation rules of Law No. 1 of 2013 to strengthen sharia cooperation is giving an authority to the National Sharia Council, that is Indonesian Ulema Council for developing, regulating, and supervising sharia-based microfinance institutions in Indonesia.